PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2016) - Veronika, Aldina Putri; Sari, Inayah Adi; Raharjo, Teguh Budi (PERMANA, 2017)
The purpose of this study is 1) to determine the effect of good corporate governance (audit committee, managerial ownership, institutional ownership, and proportion of independent commissioners) and company size simultaneously on financial performance 2) to determine the effect of the audit committee on financial performance 3) to determine the influence managerial ownership of financial performance 4) to determine the effect of institutional ownership on financial performance 5) to determine the effect of the proportion of independent commissioners on financial performance and 6) to determine the effect of firm size on financial performance. The data collection method used in this study is documentation. While the data analysis method used is testing classical assumptions, multiple linear regression analysis, hypothesis testing and coefficient of determination. Based on the results of testing the first hypothesis using the simultaneous significance test it can be concluded that there is a significant effect of the audit committee, managerial ownership, institutional ownership, and the proportion of independent commissioners and company size simultaneously on financial performance so that the first hypothesis is accepted. The results of testing the second hypothesis can be concluded that there is no significant effect of the audit committee on financial performance so that the second hypothesis is rejected. The results of testing the third hypothesis can be concluded that there is no significant effect managerial ownership of financial performance so that the third hypothesis is rejected truth. The results of testing the fourth hypothesis can be concluded that there is no significant effect of institutional ownership on financial performance so that the fourth hypothesis is rejected. The results of testing the fifth hypothesis can be concluded that there is a significant effect the proportion of independent commissioners on financial performance so that the fifth hypothesis is accepted. The results of testing the sixth hypothesis can be concluded that there is no significant effect of company size on financial performance so that the sixth hypothesis is rejected.  Keywords: audit committee, managerial ownership, institutional ownership, proportion of independent commissioners, company size, financial performance